MET IHC Is a Poor Screen for MET Amplification or MET Exon 14 Mutations in Lung Adenocarcinomas: Data from a Tri-Institutional Cohort of the Lung Cancer Mutation Consortium - Guo, Robin; Berry, Lynne D.; Aisner, Dara L.; Sheren, Jamie; Boyle, Theresa; Bunn, Paul A.; Johnson, Bruce E.; Kwiatkowski, David J.; Drilon, Alexander; Sholl, Lynette M.; Kris, Mark G. (Journal of thoracic oncology, 2019)
MNNG HOS Transforming gene (MET) amplification and MET exon 14 (METex14) alterations in lung cancers affect sensitivity to MET proto-oncogene, receptor tyrosine kinase (MET [also known by the alias hepatocyte growth factor receptor]) inhibitors. Fluorescence in situ hybridization (FISH), next-generation sequencing (NGS), and immunohistochemistry (IHC) have been used to evaluate MET dependency. Here, we have determined the association of MET IHC with METex14 mutations and MET amplification. We collected data on a tri-institutional cohort from the Lung Cancer Mutation Consortium. All patients had metastatic lung adenocarcinomas and no prior targeted therapies. MET IHC positivity was defined by an H-score of 200 or higher using SP44 antibody. MET amplification was defined by copy number fold change of 1.8x or more with use of NGS or a MET-to–centromere of chromosome 7 ratio greater than 2.2 with use of FISH. We tested tissue from 181 patients for MET IHC, MET amplification, and METex14 mutations. Overall, 71 of 181 patients (39%) were MET IHC–positive, three of 181 (2%) were MET-amplified, and two of 181 (1%) harbored METex14 mutations. Of the MET-amplified cases, two were FISH positive with MET-to–centromere of chromosome 7 ratios of 3.1 and 3.3, one case was NGS positive with a fold change of 4.4x, and one of the three cases was MET IHC–positive. Of the 71 IHC-positive cases, one (1%) was MET-amplified and two (3%) were METex14-mutated. Of the MET IHC–negative cases, two of 110 (2%) were MET-amplified. In this study, nearly all MET IHC–positive cases were negative for MET amplification or METex14 mutations. MET IHC can also miss patients with MET amplification. The limited number of MET-amplified cases in this cohort makes it challenging to demonstrate an association between MET IHC and MET amplification. Nevertheless, IHC appears to be an inefficient screen for these genomic changes. MET amplification or METex14 mutations can best be detected by FISH and a multiplex NGS panel.